Domain wall control in wire-tube nanoelements - Neumann, R. F.; Bahiana, M.; Vargas, N. M.; Altbir, Dora; Allende, S.; Goerlitz, D.; Nielsch, Kornelius (Applied Physics Letters, 2013)
The possibility of a three-state nanoelement, composed by a wire and a tube, is investigated by means of Monte Carlo simulations. The desired behavior may be identified by a step or plateau in the hysteresis curve, corresponding to a partial pinning of the domain wall at the interface between wire and tube sections. This step may be augmented in segmented nanoelements with large coercivity difference between the sections. Different possibilities, such as geometry and choice of materials, are explored. © 2013 AIP Publishing LLC.
CRIS-Team Scopus Importer:2023-03-20